Improved light-induced cell detachment on rutile TiO2 nanodot films. (15th October 2015) - Cheng, Kui; Sun, Yu; Wan, Hongping; Wang, Xiaozhao; Weng, Wenjian; Lin, Jun; Wang, Huiming
Graphical abstract: Abstract: Anatase TiO2 nanodot films have been found to be able to release cells under light illumination with excellent efficiency and safety. In the present study, we investigated the effects of rutile contents in TiO2 nanodot films on such light induced cell detachment behavior. The results showed that TiO2 nanodot films with different contents of rutile phase have been prepared successfully. The content of rutile phase increased with the increase in calcination temperature. All films possessed good cell adhesion but there was a decrease in cell proliferation with the increasing content of rutile phase. Single cell detachment assay showed that the films with high rutile contents (calcined at 900 °C and 1100 °C) showed better cell detachment performance. That was ascribed to the changes of the secondary structure of extracellular proteins adsorbed on the nanodot surface after ultraviolet (365 nm, UV365) illumination. In addition, cell sheets detached through UV365 illumination maintained high activity and could be further used in tissue engineering. The present work showed that the existence of rutile phase is helpful in cell detachment behavior and it could be utilized to optimize light-induced cell detachment behavior. Statement of Significance: This work discovers that the presence of rutile phase in TiO2 nanodot films could improve the light-induced cell detachment behavior, although rutile phase is inferior to anatase phase on light induced superhydrophilicity. That strongly supported that the behaviors of adsorbed proteins are crucial in acquiring cell sheet with light illumination. In fact, the state and behavior of adsorbed protein greatly affect the interaction between biomaterials and living cells. Therefore, we consider this work is not only important in harvesting cells or cell sheets through light illumination, but also helpful in further understanding of interaction between biomaterials and cells.